Tribocorrosion resistance of the CoCrFeNiMox laser-clad coatings on Ti6Al4V in three different circumstances - Xiao Sun; Jun Li; Kang Wei; Yanan Yan; Soowohn Lee; Jianguo Tang (Journal of Materials Research and Technology)
The CoCrFeNiMox (x = 0, 0.5, 1) coatings were prepared on Ti6Al4V (TC4) by laser cladding. The coatings were composed of α(Ti) and Ti2Ni as the matrix and TiC as the reinforcement. With the increase in Mo content, the morphology of TiC was transformed from coarse dendrites + fine flower-like particles (Coating Mo0), into fine flower-like particles + finer equiaxed particles with higher volume fraction (Coating Mo0.5), finally into fine flower-like particles + finer equiaxed particles with higher volume fraction (Coating Mo1). The average microhardness of the coatings presented the upward tendency with the increase in Mo content. However, Corrosion resistance of the coatings in three corrosion environments demonstrated the first upward and then downward tendency, which mainly depended on two factors corresponding to the formation difficulty of passivation film, the compactness and stress of formed passivation film. The introduction of Mo accelerated the formation of passivation film and promoted its compactness, but increased its cracking susceptibility, resulting in the most outstanding corrosion resistance obtained in Coating Mo0.5. Wear resistance of the coatings also presented the similar change in three corrosion environments, namely the lowest wear rate was acquired in Coating Mo0.5. The introduction of Mo contributed to the improvement in resistance to micro-cutting due to the increase in hardness of the coatings, accompanied by which the reduction in plastic deformation resulted in the passivation film was easily exfoliated and broken. This further caused the formation of more micro-galvanic cells, accelerating the active dissolution. Wear mechanism of the coatings was determined as micro-cutting + active dissolution + oxidation + brittle micro-peeling.